Cottone's practical infection control in dentistry 2026-02-16T03:41:04+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Molinari, John A.; Harte, Jennifer A. (Lippincott William & Wilkins, 2010)

(untitled)
Now in its Third Edition, this book is a primary, comprehensive infection control text for students in the dental professions. Using the latest scientific and clinical evidence and current infection control guidelines, the book presents easy-to-follow protocols as components of a basic infection control routine. This Third Edition has been thoroughly updated and contains more photographs and tables. A glossary of terminology and acronyms appears at the beginning of each chapter